1995
DOI: 10.1002/1097-0142(19951015)76:8<1377::aid-cncr2820760813>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy-related pericardial effusion. 127 cases from the roswell park cancer institute

Abstract: Background. Malignancy‐related pericardial effusions may represent a terminal event in patients with therapeutically unresponsive disease. However, select patients with malignancies sensitive to available therapies may achieve significant improvement in palliation and long term survival with prompt recognition and appropriate intervention. Methods. From 1968 to 1994, 150 invasive procedures were performed for the treatment or diagnosis of pericardial effusion in 127 patients with underlying malignancies. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
8

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(78 citation statements)
references
References 71 publications
4
66
0
8
Order By: Relevance
“…Most of our patients revealed electrocardiographic abnormalities (84%), although they were of a nonspecific type. There was a high incidence of low-voltage complexes, as seen also in the literature 5 , reflecting a diffuse involvement. In our series, there was a high positivity for pericardium biopsy associated with cytological analysis of the pericardial effusion (84%).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Most of our patients revealed electrocardiographic abnormalities (84%), although they were of a nonspecific type. There was a high incidence of low-voltage complexes, as seen also in the literature 5 , reflecting a diffuse involvement. In our series, there was a high positivity for pericardium biopsy associated with cytological analysis of the pericardial effusion (84%).…”
Section: Discussionsupporting
confidence: 71%
“…Frequently, the pericardial neoplastic disease has a subclinical course, thus the in vivo diagnosis many times is not suspected 4 . Autopsy studies revealed that only 20% to 64% of patients had a confirmed diagnosis while still alive 5,6 . In the majority of patients, chest radiography is abnormal, and pleural effusion is the most frequent feature 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic spread to serosal surfaces involves primarily the pleural cavity, where breast cancer is the etiology of approximately 25% of malignant effusions (2,3). However, breast carcinoma metastasis may be infrequently found in the pericardial and peritoneal cavity as well (4). Involvement of the pleural cavity by breast carcinoma may occur at any point of time of the clinical course and may be the sole manifestation of metastatic disease (5).…”
Section: Introductionmentioning
confidence: 99%
“…In such patients, the mechanisms of development of pericardial effusion include direct metastasis to the pericardium, toxicity of chemotherapy or radiation, lymphatic drainage impairment, hypoalbuminemia and opportunistic infections. Malignant or radiation-induced effusions have been identified in most cases (17,18), whereas infection is thought to be a rare etiology of pericardial effusions in cancer patients.…”
Section: Discussionmentioning
confidence: 99%